Immune tolerance of mice allogenic tooth transplantation induced by immature dendritic cells - Li, Wenying (Int J Clin Exp Med, 2015)
As a common procedure in dentistry for replacing a missing tooth, allogenic tooth transplantation has encountered many difficulties in the clinical application because of immunological rejection. It is hypothesized that immature dendritic cell injection might be a potential alternative method to avoid or alleviate immunological rejection in allogenic tooth transplantation. To test this hypothesis, a mouse model of allogenic and autogeneic tooth transplantation was to established test the immunosuppressive effect of immature dendritic cells (imDCs) derived from donor bone marrows on transplant rejection in allogenic tooth transplantation. 2 × 10(6) imDCs generated with 50 U/ml GM-CSF were injected to each recipient mouse by two ways: tail vein injection 7 days before transplantation or regional dermal injection at day 0 and day 3 after transplantation. Groups of autogeneic tooth transplantation and allogenic tooth transplantation without any treatment were set as control groups. The effects were evaluated with histopathology and immunohistochemistry. We found there was no obvious rejection in autogeneic tooth transplantation group; tail intravenous injection group showed obviously alleviated rejection while local injection group and none-treatment allogenic tooth transplantation group both showed severe rejection. Our results suggested that the rejection of allogenic tooth transplantation could be alleviated by tail vein injection of donor bone marrow-derived imDCs though it could not be completely eliminated. The clinical application of imDCs in allogenic tooth transplantation still needs further deep research.